2024
DOI: 10.1109/tbme.2023.3292032
|View full text |Cite
|
Sign up to set email alerts
|

Continuous A-Mode Ultrasound-Based Prediction of Transfemoral Amputee Prosthesis Kinematics Across Different Ambulation Tasks

Abstract: Volitional control systems for powered prostheses require the detection of user intent to operate in real life scenarios. Ambulation mode classification has been proposed to address this issue. However, these approaches introduce discrete labels to the otherwise continuous task that is ambulation. An alternative approach is to provide users with direct, voluntary control of the powered prosthesis motion. Surface electromyography (EMG) sensors have been proposed for this task, but poor signalto-noise ratios and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…New research has also shown the ability of US to isolate spatially-resolved motor unit action potentials [60]. SMG has been demonstrated to be feasible for controlling both upper [61]- [64] and lower [65] prosthetic limbs. In addition, preliminary work is demonstrating the ability for SMG to decode the intent of users with spinal cord injury [66].…”
Section: E Wearable Us For Rehabilitation Engineering and Neuroengine...mentioning
confidence: 99%
“…New research has also shown the ability of US to isolate spatially-resolved motor unit action potentials [60]. SMG has been demonstrated to be feasible for controlling both upper [61]- [64] and lower [65] prosthetic limbs. In addition, preliminary work is demonstrating the ability for SMG to decode the intent of users with spinal cord injury [66].…”
Section: E Wearable Us For Rehabilitation Engineering and Neuroengine...mentioning
confidence: 99%